Juridical Reasoning for the Distribution of Pharmaceutical Preparations that Failed the Efficacy Test in Court Decisions - Ferry Irawan Febriansyah; Richard Tomlins; Ulya Shafa Firdausi; Yusuf Adam Hilman (Jurnal Jurisprudence, 2024)
ABSTRACT Purpose of thestudy (Tujuan) : The purpose of this research is to determine the judge's considerations in imposing sanctions on pharmaceutical distributors who do not meet the efficacy and quality standards by the Ponorogo district court decision Number 115/Pid.Sus/2023/PN Png using juridical analysis.  Methodology (Metodologi): The methodology used is a normative research method or library research method. Results (Temuan): The results of this research are that there are cases of distribution of drugs that do not match the efficacy and quality, violating the protection rights of consumers. The government and BPOM are expected to pay more attention to the pharmaceutical production process and provide education to the lay public in the pharmaceutical sector so that the public obtain safe and quality pharmaceutical products. Ponorogo District Court Decision Number 115/Pid, Sus/2023/PN Png The panel of judges considered evidence, legal interpretation, and ethics during the trial. This case violates Law Number 36 of 2009 Article 196 concerning Health. By considering this, circumstances emerged that mitigated and aggravated the defendant and also used the theory of will and the theory of knowledge so that he was charged with imprisonment for 1 (one) year and a fine of IDR 5,000,000.00 (five million rupiah) provided that the fine was not paid to be replaced by imprisonment for one month. The decision at the Ponorogo District Court provides a solid foundation for future courts in handling similar cases. Applications of this study (Kegunaan): The use of this research can be an in-depth understanding of the decision ratio in the Ponorogo District Court Decision for both perpetrators, legal practitioners, academics, and policymakers for future directions. Novelty/ Orginalty of this study (Kebaruan/Orisinalitas): The difference with previous studies is that the focus of this research is the location of the research, the type of drug used and the district court decision